The Development of a Real-Time Recombinase-Aid Amplification Assay for Rapid Detection of African Swine Fever Virus - Wu, Yongshu; Yang, Yang; Ru, Yi; Qin, Xiaodong; Li, Miaomiao; Zhang, Zhixiong; Zhang, Rui; Li, Yijing; Zhang, Zhidong; Li, Yanmin (Frontiers in Microbiology, 2022)
African swine fever (ASF), caused by the African swine fever virus (ASFV), is an acute, deadly, infectious disease of domestic pigs and wild boars and has a tremendous negative socioeconomic impact on the swine industry. ASF is a notifiable disease to the World Organization for Animal Health (OIE). Currently, no effective vaccine or treatment against ASF is available. Early detection and rapid diagnosis are potentially significant to control ASF spread with the emerging ASFV mutant strains and non-classical symptoms. In this study, we developed the real-time recombinase-aid amplification assay (RAA) to detect the ASFV genome rapidly. Thirty samples were detected using commercial lysis buffer for DNA extraction and equipped with a portable testing instrument. The results showed that the sensitivity of RAA was as 103 copies per reaction at 95% probability in 9 min, at 39C. The method was universally specific for three strains of ASFV and no cross-reaction to other pathogens, including FMDV, CSFV, PRRSV, PCV2, PRV, and PPV. The coefficient of variation (C.V) of repetitive experiments was 0%, and the coincidence rate was 100% compared to the real-time qPCR. 123 field samples were detected by the real-time RAA assay, and the results showed that the clinical sensitivity of the real-time RAA assay was 98% compared to the real-time qPCR assay. The advantages of this method are as follows: the extraction of DNA can be performed on-site, the DNA template is directly used, a small battery-powered instrument is easily available, and the on-site diagnosis process is finished within an hour, which suggests that this assay could be used to detect different genotypes of ASFV and play a vital role in the control of ASF.